Arrunátegui Jácome,Andrea Dayanara(2023)DETERMINACIÓN DEL ÍNDICE DE MADUREZ DE LA BADEA (Passiflora quadrangularis L) PARA LA COMERCIALIZACIÓN.Quevedo.UTEQ.87p. - Arrunátegui Jácome , Andrea Dayanara (2023)
The badea (Passiflora quadrangularis L) originates in South America its fruit is large compared to another species of Passiflora, it is cultivated for sale in markets, being privileged by buyers from some countries of America for its fresh juice, dessert or jams and its excellent nutritional properties as foods that favor the proper functioning of the nervous system for its serotonin content is ideal for infants by amount of vitamin E, Iron and calcium percentage (%) This fruit can be used in full. The objective of this research was to determine the maturity indices of badea (Passiflora quadrangularis L) for marketing. For this purpose, the physicochemical properties of the badea (Passiflora quadrangularis L) were analyzed: (Weight size, diameter, percentage of edible portion of the pulp, moisture, pH, soluble solids (º Brix), acidity. From the results obtained were determed statistically significant differences between the different days of state of maturity of the fruit the value of percentage in green fruits of 78.8% pintona 80.1% and ripe 82.3%, the pH of the pulp of the badea goes from values of 5.58 to 6.31, the values of ° Brix increased, decreasing on day 5; from day 8 its value increased until the end of day 11 of 4.33 to 7.29 ° Brix, unlike pH and ° Brix, the acidity of the fruit was decreasing from day 1, until day 11. It was determined that the maturity index suitable for commercialization is 8.42 ± 0.77 % these values were obtained from day 4.